Chemotherapy-induced pain is promoted by enhanced spinal adenosine kinase levels through astrocyte-dependent mechanisms. Issue 6 (June 2018) - Wahlman, Carrie; Doyle, Timothy M.; Little, Joshua W.; Luongo, Livio; Janes, Kali; Chen, Zhoumou; Esposito, Emanuela; Tosh, Dilip K.; Cuzzocrea, Salvatore; Jacobson, Kenneth A.; Salvemini, Daniela
Abstract : Abstract: Development of chemotherapy-induced neuropathic pain (CINP) compromises the use of chemotherapy and greatly impacts thousands of lives. Unfortunately, there are no Food and Drug Administration–approved drugs to prevent or treat CINP. Neuropathological changes within CNS, including neuroinflammation and increased neuronal excitability, are driven by alterations in neuro-glia communication; but, the molecular signaling pathways remain largely unexplored. Adenosine is a potent neuroprotective purine nucleoside released to counteract the consequences of these neuropathological changes. Adenosine signaling at its adenosine receptors (ARs) is dictated by adenosine kinase (ADK) in astrocytes, which provides a cellular sink for the removal of extracellular adenosine. We now demonstrate that chemotherapy (oxaliplatin) in rodents caused ADK overexpression in reactive astrocytes and reduced adenosine signaling at the A3 AR subtype (A3 AR) within the spinal cord. Dysregulation of ADK and A3 AR signaling was associated with increased proinflammatory and neuroexcitatory interleukin-1β expression and activation of nucleotide-binding oligomerization domain-like receptor protein 3 inflammasome, but not putative oxaliplatin-associated GSK3β transcriptional regulation. Intrathecal administration of the highly selective A3 AR agonist MRS5698 attenuated IL-1β production and increased the expression of potent anti-inflammatory and neuroprotective IL-10. The effects of MRS5698 were blocked by attenuating IL-10 signaling in rats with intrathecal neutralizing IL-10 antibody and in IL-10 −/− knockout mice. These findings provide new molecular insights implicating astrocyte-based ADK-adenosine axis and nucleotide-binding oligomerization domain-like receptor protein 3 in the development of CINP and IL-10 in the mechanism of action of A3 AR agonists. These findings strengthen the pharmacological rationale for clinical evaluation of A3 AR agonists already in advanced clinical trials as anticancer agents as an adjunct to chemotherapy. Abstract : Results of our study provide the first evidence that oxaliplatin-induced neuropathic pain is driven by increased astrocyte adenosine kinase and decreased A3 adenosine receptor signaling.